Transient increase in DNA strand breaks in car refinishing spray painters - Fuchs, J.; Hengstler, J. G.; Hummrich, F.; Oesch, F. (Scandinavian Journal of Work, Environment & Health, 1996)
' ' OBJECTIVES ': 'Genotoxic risk was evaluated for spray painters possibly exposed to polyester resins and acrylic enamel-based paints in automotive body repair shops.' ' METHODS ': 'DNA (deoxyribonucleic acid) strand breaks and alkali-labile sites were measured in peripheral mononuclear blood cells ex vivo using the alkaline elution method. Samples of venous blood were taken on Monday after a free weekend and again on Friday from 38 male and 1 female spray painters and compared with the blood samples from 36 male and 3 female referents. The elution rate of each DNA sample was standardized by dividing it by the elution rate obtained from simultaneously sampled untreated Chinese hamster V79 cells.' ' RESULTS ': 'The spray painters showed a significantly (P
Keywords: alkaline elution; biomonitoring; DNA damage; human mononuclear blood cells; safety provision